2009
DOI: 10.1142/s1756973709000037
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Crystal Plasticity Fe System for Microforming Simulation

Abstract: Based on Voronoi tessellation and the probability theory, a VGRAIN system is created for the generation of grains and grain boundaries for micromaterials. This system requires physical parameters obtained from microstructures of materials, such as the average, minimum and maximum grain sizes. Numerical procedures have been established to link the physical parameters of a material to the control variable in a gamma distribution equation and a method has been developed to solve the probability equation. These ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Comparison of the two descriptive models, both of which describe the relationship between the grain area distribution parameter and the regularity parameter . The dotted line is the model proposed in [35] and [36], and the solid line is the improved model: (a) Global quality, (b) local quality. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Labelmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of the two descriptive models, both of which describe the relationship between the grain area distribution parameter and the regularity parameter . The dotted line is the model proposed in [35] and [36], and the solid line is the improved model: (a) Global quality, (b) local quality. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: Labelmentioning
confidence: 99%
“…In the beginning, Zhu et al [34] introduced a 'regularity parameter' to quantify the degree of grain size uniformity for a VT. Then, Ho et al [35] and Cao et al [36] adopted this regularity parameter to inversely produce VTs with specified regularities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the scatter effect of the flow stress curve increases with increasing grain size and the achieved scatter range had a good agreement with the experimental result. Voronoi tessellation can be adopted to describe the polycrystalline aggregate [25][26][27]. Lu et al [25] proposed a mixed material model based on modified Hall-Peth relationship, surface layer model, and grained heterogeneity (e.g., grain size, shape, and deformability).…”
Section: Flow Behaviormentioning
confidence: 99%
“…The value of the regularity parameter ranges from 0 to 1, corresponding to a Poisson Voronoi tessellation (PVT) and a regular hexagonal tessellation, respectively. Ho et al [32] and Cao et al [33] adopted this regularity parameter as a control parameter and proposed a scheme to produce Voronoi tessellations with specified regularity.…”
Section: Introductionmentioning
confidence: 99%